2009
DOI: 10.7150/ijms.6.28
|View full text |Cite
|
Sign up to set email alerts
|

Sustained High Quality of Life in a 5-Year Long Term Follow-up after Successful Ablation for Supra-Ventricular Tachycardia. Results from a large Retrospective Patient Cohort

Abstract: Introduction: The ablation of supraventricular tachycardias (SVT) using radiofrequency energy (RF) is a procedure with a high primary success rate. However, there is a scarcity of data regarding the long term outcome, particularly with respect to quality of life (QoL).Methods and Results: In this retrospective single-center study, 454 patients who underwent ablation of SVT between 2002 and 2007 received a detailed questionnaire addressing matters of QoL. The questionnaire was a modified ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
2
24
0
1
Order By: Relevance
“…The findings from this observational study indicate that waiting for RFA as a treatment for cardiac tachyarrhythmia may be associated with adverse impact in multiple dimensions. The quality of life data are consistent with those from other investigators who have looked at the impact of the procedure itself in a variety of arrhythmic substrates . However, we encountered relatively few studies in the published literature reporting on the psychological burden associated with arrhythmias themselves.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings from this observational study indicate that waiting for RFA as a treatment for cardiac tachyarrhythmia may be associated with adverse impact in multiple dimensions. The quality of life data are consistent with those from other investigators who have looked at the impact of the procedure itself in a variety of arrhythmic substrates . However, we encountered relatively few studies in the published literature reporting on the psychological burden associated with arrhythmias themselves.…”
Section: Discussionsupporting
confidence: 85%
“…The quality of life data are consistent with those from other investigators who have looked at the impact of the procedure itself in a variety of arrhythmic substrates. [17][18][19][20][21][22][23][24][25][26] However, we encountered relatively few studies in the published literature reporting on the psychological burden associated with arrhythmias themselves. One small study including 43 patients with supraventricular tachycardia (SVT) explored functional ability, coping, health locus of control, pain, and psychosocial adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…10 When AF and atrial flutter coexist, 1 randomized study demonstrated that at 1-year follow-up, greater success in terms of arrhythmia suppression and quality-of-life score resulted from AF ablation (with or without atrial flutter ablation) than from atrial flutter ablation alone. 381 It may be that AF ablation alone is sufficient to control both arrhythmias, although CTI ablation reduced the early postablation arrhythmia recurrence rate. No prospective RCTs have compared the efficacy or safety of antiarrhythmic drugs with that of catheter ablation for non-CTI-dependent atrial flutter.…”
Section: 382mentioning
confidence: 99%
“…16,17 There are retrospective studies in which patients with supraventricular tachycardia (SVT) were asked to grade their HRQOL after RFA and compare it with how they recall feeling before treatment. 18,19 However, with that methodology there is an obvious risk for bias recall, because patients' rating of HRQOL would be influenced by the ablation procedure, the outcome of the RFA, and the time the assessment is made. HRQOL preferably should be evaluated prospectively.…”
mentioning
confidence: 98%